Macrophages and fibrosis: how resident and infiltrating mononuclear phagocytes account for organ injury, regeneration or atrophy - Long, Hao; Lichtnekert, Julia; Andrassy, Joachim; Schraml, Barbara U.; Romagnani, Paola; Anders, Hans-Joachim (Frontiers in Immunology, 2023)
Mononuclear phagocytes (MP), i.e., monocytes, macrophages, and dendritic cells (DCs), are essential for immune homeostasis via their capacities to clear pathogens, pathogen components, and non-infectious particles. However, tissue injury-related changes in local microenvironments activate resident and infiltrating MP towards pro-inflammatory phenotypes that contribute to inflammation by secreting additional inflammatory mediators. Efficient control of injurious factors leads to a switch of MP phenotype, which changes the microenvironment towards the resolution of inflammation. In the same way, MP endorses adaptive structural responses leading to either compensatory hypertrophy of surviving cells, tissue regeneration from local tissue progenitor cells, or tissue fibrosis and atrophy. Under certain circumstances, MP contribute to the reversal of tissue fibrosis by clearance of the extracellular matrix. Here we give an update on the tissue microenvironment-related factors that, upon tissue injury, instruct resident and infiltrating MP how to support host defense and recover tissue function and integrity. We propose that MP are not intrinsically active drivers of organ injury and dysfunction but dynamic amplifiers (and biomarkers) of specific tissue microenvironments that vary across spatial and temporal contexts. Therefore, MP receptors are frequently redundant and suboptimal targets for specific therapeutic interventions compared to molecular targets upstream in adaptive humoral or cellular stress response pathways that influence tissue milieus at a contextual level.